Mapeando a escrita de estudantes do ensino fundamental: em foco o artigo de opinião - Silva, Cleiton Reisdorfer (2019)
In this work, we seek to analyze the recurrent linguistic-discursive characteristics in opinion articles produced by students of basic education. As a theoretical contribution to the analysis of the corpus, we start from the notion of genre of the Social-rhetoric (MILLLER, 1984, 2014; BAZERMAN, 2011a; 2011b; 2015), CARS Model (SWALES, 1990) and the concepts of the Systemic-Functional Grammar (SFG) (HALLYDAY, MATTHIESSEN, 2014).The research corpus consists of 59 articles of opinion produced by students of the Ninth Year of Elementary Education in the context of the classroom. The results of the analysis indicate that the rhetorical structure of the opinion article produced by these students presents movements and characteristic steps of the communicative situation of the production of the texts. We verified that the opinion articles written by the students present the following movements: 1 - Contextualization; 2 - Presentation of the thesis; 3 - Defense of the thesis; 4 - Synthesis and reiteration. Quantifying the data, we verified that students use Movements 2 and 3 more frequently, but they present difficulties in contextualizing and synthesizing their positions. The analysis of ideational meanings has shown that students use material processes associated with participants generic names to indicate facts and actions, identify and attribute characteristics to text field, to a semiotic object or semiotic abstraction through relational processes, and position themselves using personal pronouns associated with relational processes. The analysis of interpersonal resources indicated that, among these resources, students predominantly use modal negations and verbs in texts. Finally, the analysis showed that the texts present a rhetorical structure that is a characteristic of that communicative situation, characterizing the texts as scholarly opinion articles. The observed discursive and linguistic elements evidence the need for greater study and deepening of this genre in a school context.